Besari, Humanity, and Tegalsarian Network: An Introductory Note - Dawam Multazamy Rohmatulloh; Muhammad Muchlish Huda (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2023)
We are delighted to introduce and launch Besari: Journal of Social and Cultural Studies through this inaugural article. Here we briefly present the legacy left by Kiai Ageng Muhammad Besari of Pesantren Tegalsari in Ponorogo, Indonesia, and its significance and importance on current ideas and realities, especially about the development of Islam in Indonesia and Indonesian Islam. By perpetuating the name of the kiai as this journal name, we do not only expect to inherit the legacy, but also understand the value behind the name, Besari, which contains concepts of ukhuwah basyariyah, the brotherhood of humanity, Islam as a religion of salvation, and humanitarian Islam. Therefore, through this inaugural article, we are delighted to introduce Besari: Journal of Social and Cultural Studies to those feeling invited to answer the call for humanity, call for Besari.